On combined optical solitons of the one-dimensional Schrodinger's equation with time dependent coefficients - Kilic, Bulent; İnç, Mustafa; Baleanu, Dumitru (De Gruyter Open Ltd, 2016)
This paper integrates dispersive optical solitons in special optical metamaterials with a time dependent coefficient. We obtained some optical solitons of the aforementioned equation. It is shown that the examined dependent coefficients are affected by the velocity of the wave. The first integral method (FIM) and ansatz method are applied to reach the optical soliton solutions of the one-dimensional nonlinear Schrodinger's equation (NLSE) with time dependent coefficients.
Keywords: FIM; metamaterial; optical soliton